Analisis Pengaruh Lingkungan Sekolah terhadap Minat dan Motivasi Belajar Siswa Sekolah Dasar - Khafidotul Kirom Nuzulin Khumasi; Nurul Fadhilah; Salsabila Maulida Putri; Amalia Dwi Nur Hikmah; Eka Nuraeni; Gigih Winandika (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the extent to which the school environment influences students’ interests and motivation in learning at SDN Maos Lor 04. The main research subjects were grade V students, and teachers as supporting informants. The school environment, which includes the physical condition of the building, social interaction, and availability of learning facilities, plays an important role in creating a positive and enjoyable lerning atmosphere, This study uses a descriptive qualitative method, with data collection techniques through observation, interviews, and documentation. The results of the study indicate that a clean, orderly, safe school atmosphere, as well as a harmonious relationship between teachers and students can encourage enthusiasm for learning and increase student involvement in the learning process. Conversely, a less supportive school environment tends to reduce student motivation and active participation. Students’ interests and desires in learning are also influenced by other factors such as family involvement, emotional support, and implementation of appropriate learning strategies. Therefore, synergy between schools, teachers, and parents is needed to create a conductive and meaningful learning environment for student development.